Juvenile hyaline fibromatosis: A 10-year follow-up - Esra Baltacioglu; Esra Guzeldemir; Erkan Sukuroglu; Kadriye Yildiz; Pinar Yuva; Güven Aydin; Naci Karacal (Wolters Kluwer Medknow Publications, 2017)
Juvenile hyaline fibromatosis (JHF) is a rare hereditary disease with an autosomal recessive transmission. JHF is characterized by papulonodular skin lesions, osteolytic bone lesions, flexural joint contractures, and gingival hyperplasia and usually diagnosed in infancy or early childhood. JHF is thought to be a disorder of collagen metabolism and characterized by homogenous amorphous eosinophilic material and fibrous tissue. We report the case of a 14-year-old male child with multiple papulonodular skin lesions, progressive flexion contractures of joints, and severe gingival hyperplasia, with a 10-year follow-up. Although the lesions were totally removed thrice during the last 10 years, they recurred rigorously.